Transcription factor Sox11 is essential for both embryonic and adult neurogenesis. Issue 6 (28th April 2013) - Wang, Yong; Lin, Lu; Lai, Helen; Parada, Luis F.; Lei, Lei
<x xml:space="preserve">Abstract</x> Background: Neurogenesis requires neural progenitor cell (NPC) proliferation, neuronal migration, and differentiation. During embryonic development, neurons are generated in specific areas of the developing neuroepithelium and migrate to their appropriate positions. In the adult brain, neurogenesis continues in the subgranular zone (SGZ) of the hippocampal dentate gyrus and the subventricular zone (SVZ) of the lateral ventricle. Although neurogenesis is fundamental to brain development and function, our understanding of the molecular mechanisms that regulate neurogenesis is still limited. Results: In this study, we generated a Sox11 floxed allele and a Sox11 null allele in mice using the Cre‐loxP technology. We first analyzed the role of the transcription factor Sox11 in embryonic neurogenesis using Sox11 null embryos. We also examined the role of Sox11 in adult hippocampal neurogenesis using Sox11 conditional knockout mice in which Sox11 is specifically deleted in adult NPCs. Sox11 null embryos developed small and disorganized brains, accompanied by transient proliferation deficits in NPCs. Deletion of Sox11 in adult NPCs blunted proliferation in the SGZ. Using functional genomics, we identified potential downstream target genes of Sox11. Conclusions: Taken together, our work provides evidence that Sox11 is required for both embryonic and adult neurogenesis, and identifies potential downstream target genes. Developmental Dynamics 242:638–653, 2013. © 2013 Wiley Periodicals, Inc.